Activity theory in information systems research and practice - theoretical underpinnings for an ISD method - Anja Mursu; Irmeli Minkkinen; Mikko Korpela (Information Research: An International Electronic Journal)
Introduction. The purpose of information systems is to facilitate work activities: here we consider how Activity Theory can be applied in information systems development. Method. The requirements for an analytical model for emancipatory, work-oriented information systems research and practice are specified. Previous research work in Activity Theory is then elaborated to satisfy these requirements in parallel with practical applications. Elaboration. Activity Analysis. and Development (ActAD) which sees work activity as a systemic entity, its constituent elements and networks of activities, is introduced and the information systems viewpoint is applied throughout the elaboration. Information systems development is modelled as an activity, applying the ActAD framework. Results. Our contribution is a participatory development model called the Activity Driven ISD Model, aimed at developing work and information systems in parallel, in three phases: understanding the present state of an activity; describing the goal state of the activity; and planning for the transformation to the goal state. Conclusion. The ActAD framework and the Activity Driven ISD Model meet six of the seven criteria set. The seventh requirement will be satisfied after the finalisation of the model. The experiences in our pilot studies concerning its applicability to the practitioners have been encouraging.